Biocatalytic Strategy for Highly Diastereo‐ and Enantioselective Synthesis of 2, 3‐Dihydrobenzofuran‐Based Tricyclic Scaffolds. (24th June 2019) - Vargas, David A.; Khade, Rahul L.; Zhang, Yong; Fasan, Rudi
Abstract: 2, 3‐Dihydrobenzofurans are key pharmacophores in many natural and synthetic bioactive molecules. A biocatalytic strategy is reported here for the highly diastereo‐ and enantioselective construction of stereochemically rich 2, 3‐dihydrobenzofurans in high enantiopurity (>99.9% de and ee), high yields, and on a preparative scale via benzofuran cyclopropanation with engineered myoglobins. Computational and structure‐reactivity studies provide insights into the mechanism of this reaction, enabling the elaboration of a stereochemical model that can rationalize the high stereoselectivity of the biocatalyst. This information was leveraged to implement a highly stereoselective route to a drug molecule and a tricyclic scaffold featuring five stereogenic centers via a single‐enzyme transformation. This work expands the biocatalytic toolbox for asymmetric C–C bond transformations and should prove useful for further development of metalloprotein catalysts for abiotic carbene transfer reactions. Abstract : Mit Eisen geschmiedet : Eine biokatalytische Strategie für die stereoselektive Cyclopropanierung von Benzfuranen führt zu enantiomerenreinen 2, 3‐Dihydrobenzofuran‐basierten 3‐gliedrigen Ringen für die Wirkstoff‐ und Naturstoffsynthese. Struktur‐Aktivitäts‐Studien geben Einblicke in den Mechanismus sowie in die proteinvermittelte Steuerung des stereochemischen Verlaufs.